2014
DOI: 10.1371/journal.pone.0089986
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Weight and Body Mass Index in Relation to Central Obesity and Metabolic Syndrome in Adulthood

Abstract: BackgroundIf preschool measures of body size routinely collected at preventive health examinations are associated with adult central obesity and metabolic syndrome, a focused use of these data for the identification of high risk children is possible. The aim of this study was to test the associations between preschool weight and body mass index (BMI) and adult BMI, central obesity and metabolic alterations.MethodsThe Northern Finland Birth Cohort 1966 (NFBC1966) (N = 4111) is a population-based cohort. Prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 27 publications
0
52
0
5
Order By: Relevance
“…(32, 51-53)They include SDB and short sleep duration, which we assessed from birth to nearly 7 years, to determine associations with subsequent obesity. Compared with children without SDB symptoms, those with the worst symptoms (peak age ≈ 2.5-3 years) had double the odds of obesity at 7, 10, and 15 years-- independent of sleep duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(32, 51-53)They include SDB and short sleep duration, which we assessed from birth to nearly 7 years, to determine associations with subsequent obesity. Compared with children without SDB symptoms, those with the worst symptoms (peak age ≈ 2.5-3 years) had double the odds of obesity at 7, 10, and 15 years-- independent of sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, our focus upon earlier childhood sleep exposures reflects evidence that sleep patterns early in childhood as compared with late childhood are more strongly associated with subsequent obesity, and that excess weight gain in early childhood tracks to later years. (32-34, 38, 51) Reverse causality is possible (ie, overweight may cause SDB). To address this, we adjusted for maternal pre-pregnancy BMI and child’s weight and length at 6 months, both of which are strong determinants of a child’s later BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence (95% uncertainty intervals) of overweight or obesity was from 16.9 (16.1-17.7)% to 23.8 (22.9-24.7)% in boys and from 16.2 (15.5-17.1)% to 22.6 (21.7-23.6)% in girls (Ng et al, 2014). Moreover, Graversen et al observed that the prevalence of overweight or obesity was consistently associated with a high body mass index (BMI) during preschool years and with adult obesity, central obesity and the early onset of metabolic syndrome (Graversen et al, 2014). Overweight children most likely become obese adults.…”
Section: Introductionmentioning
confidence: 99%
“…MetS increases the risk of cardiovascular disease (CVD) and type 2 diabetes mellitus, which are leading causes of mortality in adults [2]. Moreover, the clustering of CVD risk factors in children and adolescents has important public health implications, as the risk factors tend to track into adulthood [3,4]. Thus, early identification of MetS in children and adolescents could help to prevent progression to adulthood CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets, Early Online:[1][2][3][4][5][6] Platelets Downloaded from informahealthcare.com by Selcuk Universitesi on 01/04/15For personal use only.…”
mentioning
confidence: 99%